Cav1.3 is upregulated in osteoporosis rat model and promotes osteoclast differentiation from preosteoclast cell line RAW264.7. Issue 8 (11th February 2019) - Fan, Ping; Hu, Nan; Feng, Xiuyuan; Sun, Yining; Pu, Dan; Lv, Xiaohong; Hao, Zhiming; Li, Yang; Xue, Wujun; He, Lan
Abstract: Background: Osteoporosis (OP) is a systemic osteopathy with increased bone fragility and increased risk of fracture. Osteoclasts (OC) are the key target cells in the treatment of osteoporosis. We aimed to research the role of L ‐type calcium channel protein Cav1.3 in OC differentiation in this study. Methods: OP rat model was established to detect the expression level of Cav1.3. Tartrate‐resistant acid phosphatase assay was used to measure the differentiation of osteoclast during receptor activator of nuclear factor κ‐Β ligand (RANKL)‐induced osteoclasts formation. The expression of bone differentiation‐related proteins were detected by western blot analysis. Results: Cav1.3 is upregulated in OP rats. Knockdown of Cav1.3 inhibits the differentiation of RAW264.7. Cav1.3 regulates the cell differentiation and bone resorption of RAW264.7 during RANKL‐induced osteoclasts formation, which is accompanied by upregulation of CaMK II, p‐CERB, AP‐1, NFATC1, and NF‐κB. Conclusion: Cav1.3 plays an important role in osteoporosis and the differentiation of osteoclast, which might be involved with the bone differentiation‐related proteins. Abstract : Cav1.3 plays an important role in osteoporosis and the differentiation of osteoclast, which might be involved with the bone differentiation‐related proteins.